The east-west asymmetry of cosmic rays in high latitudes. - Burbury, Douglas William Petrie (1951)
The experimental work described in this thesis was carried out with the subject of obtaining information on the east-west asymmetry of cosmic rays in latitudes above the so called knee of the latitude intensity variation of the total cosmic ray intensity. As is explained in the Introduction, the variation of intensity with latitude and the east-west asymmetry observed between the geomagnetic equator and the latitude . of.the knee (about. 45 °geomagnetic) can be explained in terms of the effect on the primary radiation of the earth's magnetic field. At higher latitudes where little or no variation of the intensity with latitude has been found, the east-west asymmetry should vanish according to this theory. A small asymmetry has however been found by various workers, notably T.H. Johnson and F.G.P. Seidl, in latitudes above the knee. Johnson (1941) has given a theory to account for this as an effect produced by the deflection . of secondary cosmic ray particles in the earth's field. The values of the asymmetry calculated by Johnson for various zenith angles were compared with results obtained at 49° and 54° north geomagnetic latitude. Owing to the large probable errors of the experimental results, no more than a very general conclusion could be drawn from the comparison. The geomagnetic latitude of Hobart, 51.7°S, made it a suitable place to obtain results to supplement those of Seidl and Johnson, and the Hobart experiments were planned with the aim of improving the statistical precision of the results to a point where they could be used as the basis of a critical test of Johnson's theory. In the later sections of this thesis the theory is discussed in some detail. The values of the asymmetry which might be expected have been recalculated, using more recent data than that available to Johnson, graphical and -numerical methods being substituted for analytical methods in some parts of the calculations in order to use empirical data directly. It is important to establish as definitely as possible that the deflection of secondary cosmic rays between the top of the atmosphere where they are produced and sea level can lead to an asymmetry because of the apparent contradiction which the asymmetry observed in high latitudes presents to the general theory which has been found to explain the geomagnetic effects in a satisfactory manner. BY showing that Johnson's, or a similar theory can adequately explain this phenomenon, the contradiction can be removed. The history of the experimental work on this problem is as follows. In 1946, Dr. A.G. Fenton commenced work on the construction ofan automatic apparatus using a single geiger counter telescope pointing east and west alternately to measure the asymmetry. The author assisted with this work, and in 1947 when Dr. Fenton was absent on leave from the laboratory, completed the apparatus and operated it successfully to obtain results which were published in the Physical Review (Vol. 74, 589, 1948). While this setup was in operation it was decided to construct an apparatus using two geiger counter telescopes instead of one. The advantages of such an arrangement are discussed in the section in which this apparatus is described. The design and operation of this setup was almost entirely the work of the author. It was operated from the end of June 1948 until the beginning of August, 1949. At the end of 1948 the Australian National Antarctic Research Expedition became interested in the .investigation of the asymmetry and made a grant of money to enable Dr. Fenton's brother, Mr. K.B. Fenton, to extend the work to geomagnetic latitude 60.7°S by operating an apparatus Similar to the Hobart one on Macquarie Island in 1950 and possibly 1951. Problems incident to the operation of apparatus remote from the facilities available in the laboratory made the construction of this apparatus a project of considerable magniitude, and it was accordingly shared between Dr. Fenton, his brother, and the author. Dr. Fenton Who had worked on the properties of geiger counters in Birmingham undertook to construct the counters required,. while his brother took responsibility for the design and construction of suitable recording circuits. The contributions of the author to this work are described in Part II, and included the design of an automatic 35mm. camera to record the results, the modification of a turntable previously used in a Predictor unit to make it suitable for mounting of the apparatus, and the design of control gear to make the setup automatic in operation. The construction of this apparatus was successfully completed in time for it to be shipped to Macquarie Island in April, 1950. Between April and June, 1950, the Hobart apparatus was modified to include several improvements. The most important of these wee the fitting of larger trays of geiger counters to increase the counting rates, which was possible because of the improved supply of counters available at that time. The modifications were completed by the tithe the Macquarie Island gear was ready for use, and the two sets were put into operation on parallel schedules at the end of June, 1950.